(untitled) (World Science, 2021)
The development of road transport, both economically and socially, is of great importance for humanity. But along with the tremendous benefits and unlimited potential of road transport, there are many problems, particularly with its operation in human settlements, particularly in cities. These problems are related to the oversaturation of the road network of cities with road transport, which leads to a decrease in speed, congestion, increased travel time. Ensuring the required capacity of the site is the main indicator of creating conditions for the efficient functioning of the transport system of cities. Each section has its own planning features that allow the car to move at an acceptable speed and at the same time not create any situations that could lead to the formation of congestion. It is known that the lower the speed, the greater the time spent. Speed is one of the most important indicators of traffic flow. Any reduction in the speed of traffic flows compared to the permitted leads to economic losses. And if we consider the reduction of speed, taking into account the stop in motion (delay), it leads to much greater economic losses.